The effect of corporate governance compliance and sustainability risk management (SRM) success factors on firm survival - Abdul Manab, Norlida; Abdul Aziz, Nazliatul Aniza; Othman, Siti Norezam (ISDS LLC, 2017)
The aim of this paper is to examine whether corporate governance compliance and sustainability risk management (SRM) success factors have an impact on firm survival.Corporate governance and risk management have become central issues for all types of organisations.The practices of corporate governance and risk management are interrelated and closely linked.The sustainability and the improvements of the firm’s performance and survival are highly dependent on the effective role of both components.A survey questionnaire was distributed to the individuals responsible for firms’ risk management activities in environmentally sensitive listed firms in Malaysia.Out of 105 questionnaires distributed, 53 responded with a response rate of 50.5 per cent. Partial Least Squares Structural Equation Modelling (PLS-SEM) technique was used to analyse the hypothetical model developed in this study. Corporate governance compliance has been found as one of the main reasons for SRM adoption. The results also revealed that corporate governance compliance, leadership and risk culture have an impact on firms’ survival.The findings from this study enable firms to better understand the importance of corporate governance compliance and reinforcing leadership, risk culture and risk resilience to successfully implement SRM program.